Physical education curriculums in the educational institutions of Zakarpattia in the 20-30 years of the XX century - Trifan A. (Kharkov National Pedagogical University, 2010)
The questions of history of introduction of the programs are analysed on a physical culture in educational establishments of Zakarpattia in 20-30 years of XX age. From 1924 on Zakarpattia the school programs on physical education were used only in incomplete middle schools and gymnasia. Basis of on-line tutorials and plans of that time was made by the elements of physical exercises, developed the Czech specialists. Directions of taking approach are rotined to school program development in modern education. A decision of the expounded problems in planning is necessary pre-condition of successful and effective educational process.